(3JfRjg GdCfHjGA Yf JSajg GdCZHjGAs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3dhbYhG ai Jjg Cdai HecQ GdTjWGf hYGeI GdedGFcI GdebQHjf UdhGJ Gddg hSdGeg Ydjge CLeYjf hGdEjeGf Hge hGdGPYGf dge s
(3BNQgG (B:s
(3jfJgi HCKfGA GdcdGe Ydi eSCdI YUeI GdedGFcI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B494s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds